Effect Crud alkaloids extraction from Nicotina tabacum in same cell line: Efek Ekstraksi alkaloid kasar dari Nicotina tabacum dalam garis sel yang sama - abood, Raghad Hussein; Mohammed, Ibrahim Hadi (Indonesian Journal on Health Science and Medicine, 2025)
This study aimed to investigate some Chemical Detections of Some Compounds Nicotina tabacum in leaves of plant and the effects of the crude alkaloid  extraction  from  Nicotina  tabacum on the proliferation of MCF7  cancer cell line and MEF normal cell line. The Results the plant extraction showing alkaloid , Tannins  and glycoside  .the  effect extract on growth of tumor cell lines MCF7 showed that crude  extract revealed cytotoxicity on different cell line, and this effect depend on concentration and type of cells. The inhibition activity for tumor cell line increase with increase concentration of extract. The higher  inhibition crud  extraction  rate in MCF7  cell line was   % in concentration 15.1  µg\ml  and in 500 µ g\ml was  %,  While in MEF  cell line, the highest inhibition rate was % in 15.1 µ g\ml and   % in concentration 500 µ g\ml. The study shows that crude alkaloids  extract Nicotina tabacum have alkaloid and inhibition cell line and non inhibition normal cell.Highlight : Crude alkaloid extract from Nicotiana tabacum inhibited MCF-7 breast cancer cells in a dose-dependent manner. MEF normal cells showed minimal sensitivity, indicating selective cytotoxicity. Phytochemical screening confirmed the presence of alkaloids, flavonoids, tannins, and glycosides as active compounds. Keywords : Nicotiana Tabacum, Alkaloids, MCF-7, Cytotoxicity, Selective Inhibition